The Role of Movie Trailers and Posters as a Marketing Tool to Captivate Audiences in the Film Industry - Kruglova, Diana (2025)
This thesis explores the role of movie trailers and posters in shaping audience engagement and decision-making in the film industry. The research focuses on how emotional and rational appeals influence viewer choices, which specific trailer and poster elements affect perception across different genres, and how digital platforms have transformed the promotional landscape. To investigate these questions, a survey was conducted among 120 respondents of diverse backgrounds and nationalities. The study analyses responses regarding trailer and poster preferences, viewing habits, and platform usage. The findings reveal that emotional appeals are more influential than rational cues when it comes to choosing a film, and preferences for specific elements vary by genre. The results also confirm the dominance of digital platforms in shaping audience awareness, particularly among younger demographics. Based on these findings, the thesis proposes recommendations to enhance promotional effectiveness across genres and platforms.